Building strong music program [ a handbook for preservice and novice music teachers - Ryan, Charlene , 1971- (Rowman & Littlefield Education, 2009)
While program building is an essential, time-consuming part of every music teacher's job, students are rarely prepared for it. Ryan covers issues important to student teachers, new teachers, teachers changing schools, and teachers looking to rejuvenate their existing programs